2014
DOI: 10.1016/j.atherosclerosis.2013.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics signature improves the prediction of cardiovascular events in elderly subjects

Abstract: Aging mitochondrial dysfunction evaluated by metabolomic profiling is associated with MACEs, independently of standard predictors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
124
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(130 citation statements)
references
References 28 publications
5
124
0
1
Order By: Relevance
“…Recent research indicates that medium-and long-chain acylcarnitines predict cardiovascular events in elderly subjects. 22 By contrast, we did not find significant differences in serum levels of acylcarnitines between the study groups. However, Rizza et al 22 determined serum acylcarnitines by MRM, whereas we used precursor scan approach.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Recent research indicates that medium-and long-chain acylcarnitines predict cardiovascular events in elderly subjects. 22 By contrast, we did not find significant differences in serum levels of acylcarnitines between the study groups. However, Rizza et al 22 determined serum acylcarnitines by MRM, whereas we used precursor scan approach.…”
Section: Discussionmentioning
confidence: 52%
“…22 By contrast, we did not find significant differences in serum levels of acylcarnitines between the study groups. However, Rizza et al 22 determined serum acylcarnitines by MRM, whereas we used precursor scan approach. Furthermore, the mean age of the subjects in the aforementioned study was 85 years, 22 but in our study the mean age of the subjects was 66 years.…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, significantly different acylcarnitine profiles were observed among subjects with normal glucose tolerance, prediabetic states, or type 2 diabetes in a German study (22). Recently, several prospective studies indicated that medium-and/or long-chain acylcarnitines predicted cardiovascular events or mortality in people aged .85 years or selected patients undergoing cardiac catheterization or dialysis (23)(24)(25). However, previous European studies using the targeted BIOCRATES metabolomics platform failed to demonstrate a significant association between acylcarnitines and incident diabetes (26,27).…”
Section: Discussionmentioning
confidence: 95%
“…Rizza et al [37] have hypothesized that metabolomic profiling would identify biomarkers predicting major cardiovascular events in elderly people, and they have demonstrated that age-related mitochondrial dysfunction as evaluated by metabolomic profiling is associated with major cardiovascular events independently of standard predictors. …”
mentioning
confidence: 99%